Діяльність Г. М. Доброва як історика науки і техніки - Литвинко, А.С.; Луговський, О.Г.; Виврот, Т.М.; Хорошева, С.А.; Жабін, С.О. (Наука та наукознавство, 2018)
У статті розкрито науково-організаційну діяльність Г.М. Доброва в галузі історії науки і техніки, яка значною мірою сприяла становленню й інституалізації цього напряму в Україні. В статье раскрыта научно-организационная деятельность Г.М. Доброва в области истории науки и техники, которая в значительной степени способствовала становлению и институционализации этого направления в Украине. The article is focused on the activities and impact of G.M. Dobrov, an outstanding researcher in science and technology history studies, a correspondent member of the Academy of Sciences of the Ukrainian SSR (1988) and the International Academy of Sciences History in Paris (1965), associated with rise and institutionalization of science and technology history studies in Ukraine.